The Use of Describing Picture Strategy in Improving the Students’ Speaking Ability at UPTD SMPN 22 Barru - Wahyuni, Wahyuni; Khadijah Maming; Sudarmanto, Sudarmanto (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2022)
The purpose of this study is to improve students speaking skill because the describing picture strategy method is a good method to improve students speaking skill, students self-confidence is also better able to build, students can also be more active in class and learn in English. The researcher use pre-experimental to carry out their research. The population in this study were all students eight class of SMPN 22 Barru for academic year 2021-2022. The researcher took one class of the second grade students at SMPN 22 Barru as the sample. It was class VIII-1 consisted of 32 students. The researcher used a oral test as the instrument to get the data. To collect the data, the researcher gave students twice test, there are pre-test and post-test. The researcher gave directions to students namely describing picture in the class with a minimum speaking duration of 5 minutes for the pre-test. The researcher asked the students to describe norally the picture which given by the researcher for the post-test.The results of the data analysis of the students average scores obtained by researchers during the study were 38.3 in pre-test and 83.92 in post-test. The speaking ability of class VIII-1 students at UPTD SMPN 22 Barru improved after being taught using describing picture strategy. This is reinforced by the results of the t-test where H0 is rejected and H1 is accepted.